2022
DOI: 10.3389/fpsyt.2022.797780
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Effects of Reading and Aerobic Exercise Interventions on Inhibitory Control of College Students With Mobile Phone Addiction

Abstract: Although many previous studies have shown that short-time moderate-intensity aerobic exercise can improve one's inhibitory control, some researchers suggested that its effect on inhibitory control is small. Meanwhile, some studies have shown that reading has a positive effect on inhibitory control. Since many studies examining the effect of exercise on inhibitory control used reading as a filler task, it is important to compare their effects. The present study used the antisaccade task as a tool to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“… 94 , 95 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 Five trials studied the effect of chronic physical training on cognitive performance and eye-based measures, 96 , 118 , 119 , 120 , 121 and 18 studies investigated the influence of an acute bout of physical exercise on cognitive performance and eye-based measures. 92 , 93 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 94 , 95 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 Five trials studied the effect of chronic physical training on cognitive performance and eye-based measures, 96 , 118 , 119 , 120 , 121 and 18 studies investigated the influence of an acute bout of physical exercise on cognitive performance and eye-based measures. 92 , 93 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 …”
Section: Resultsmentioning
confidence: 99%
“… (2) n.a. (1) Pro- and antisaccade task (2) ▪ ↓ RT in antisaccade condition in tennis players vs. swimmers and non-athletes, volleyball players vs. swimmers and non-athletes, basketball players vs. non-athletes ▪ ↑ Prosaccade velocity in tennis players vs. basketball players, swimmers, and non-athletes; and volleyball players vs. non-athletes Zhou et al (2022) 134 (1) RCT with between-subject design and pretest/post-test comparisons (2) Passive CG (3) Younger adults (students) with mobile phone addiction ▪ EX: n = 15 (12 females/3 males) ▪ CON: n = 15 (11 females/4 males)] ▪ EX: 19.5 ± 0.72 years ▪ CON: 18.9 ± 0.93 years (3.1) EX: 1298.8 ± 1633.0 MET per week; CG: 1060.5 ± 1636.4 MET per week (3.2) EX: 163.0 ± 7.7cm; CG: 165.4 ± 8.2cm/51.8 ± 6.5 kg; CG: 68.9 ± 24.9 kg/EX: 19.4 ± 1.4 kg/m 2 ; CG: 24.9 ± 2.9 kg/m 2 (1) Light-to-moderate intensity (i.e., 60%–70% of predicted HR max ) (2) 15 min (1) Antisaccade task (2) ▪ ↓ Directional errors in EX and CON (post- vs. pretest) ▪ ↓ RT in CON but not in EX (post- vs. pretest) Zhou (2021) 115 (1) Cross-sectional study (2) Skilled vs . less-skilled soccer players (3) Healthy female adolescent soccer players ▪ n = 56 (16.50 ± 0.71 years) ▪ Skilled soccer players: n = 24 (24 females) ▪ Less-skilled soccer players: n = 32 (32 females) ▪ Skilled soccer players: 16.6 ± 0.7 years ▪ Less-skilled soccer players: 16.4 ± 0.7 years (3.1) n.a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that exercise can improve the inhibition and control ability deficits of individuals with MPA ( Davis et al, 2011 ). When faced with cognitive tasks, the scores of MPA of individuals doing more exercise were significantly lower ( Zhou and Wang, 2022 ). Thus, increasing self-control and physical exercise may prevent or alleviate MPA.…”
Section: Discussionmentioning
confidence: 99%
“…Common treatments include cognitive behavioral therapy ( 9 ) and motivational interventions ( 10 ), such as mental health education courses, cognitive–behavioral group counseling, and inhibitory control training. Common exercise interventions include aerobic exercise ( 11 ) and outdoor activities ( 12 ). These approaches not only allow the highly excited nerve cells to fully rest but also promote physical wellbeing; prevent conditions such as cervical spine issues, lumbar spine problems, and myopia; provide opportunities to relax; alleviate stress; reduce feelings of anxiety and depression; facilitate person-to-person communication; and enhance interpersonal relationships ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%